The main sequence of star-forming galaxies across cosmic times. Issue 1 (9th November 2022) - Popesso, P; Concas, A; Cresci, G; Belli, S; Rodighiero, G; Inami, H; Dickinson, M; Ilbert, O; Pannella, M; Elbaz, D
ABSTRACT: By compiling a comprehensive census of literature studies, we investigate the evolution of the main sequence (MS) of star-forming galaxies (SFGs) in the widest range of redshift (0 < z < 6) and stellar mass (10 8.5 –10 11.5 M⊙ ) ever probed. We convert all observations to a common calibration and find a remarkable consensus on the variation of the MS shape and normalization across cosmic time. The relation exhibits a curvature towards the high stellar masses at all redshifts. The best functional form is governed by two parameters: the evolution of the normalization and the turnover mass ( M 0 ( t )), which both evolve as a power law of the Universe age. The turn-over mass determines the MS shape. It marginally evolves with time, making the MS slightly steeper towards z ∼ 4–6. At stellar masses below M 0 ( t ), SFGs have a constant specific SFR (sSFR), while above M 0 ( t ) the sSFR is suppressed. We find that the MS is dominated by central galaxies. This allows to turn M 0 ( t ) into the corresponding host halo mass. This evolves as the halo mass threshold between cold and hot accretion regimes, as predicted by the theory of accretion, where the central galaxy is fed or starved of cold gas supply, respectively. We, thus, argue that the progressive MS bending as a function of the Universe age is caused by the lower availability of cold gas in haloes entering the hot accretion phase, in addition to black hole feedback. We also find qualitatively the same trend in the largest sample of star-forming galaxies provided by the IllustrisTNG simulation. Nevertheless, we still note large quantitative discrepancies with respect to observations, in particular at the high-mass end. These can not be easily ascribed to biases or systematics in the observed SFRs and the derived MS.